DESOXYCORTICOSTERONE ACETATE : THE POTENTIATION OF ITS ACTIVITY BY SODIUM CHLORIDE - Knowlton, Abbie I. (The Rockefeller University Press, 1947)
1. Desoxycorticosterone acetate (DCA) and NaCl, in the dosage employed in normal rats, caused renal and cardiac hypertrophy, characteristic changes in the renal tubular epithelium, atrophic changes in the subcapsular zone of the adrenal cortex, and serum electrolyte changes characterized by a rise in sodium and fall in potassium. 2. In rats rendered nephritic with a rabbit anti-rat-kidney serum, the same regimen caused similar changes. In addition, DCA given concurrently with NaCl greatly intensified the nephritic process and gave rise to striking arterial hypertension. 3. A diet, virtually sodium-free, administered to normal and nephritic rats receiving daily injections of DCA abolished or reduced to a minimum the effects of this steroid; i.e., a liberal ingestion of NaCl was essential for the potentiation of the action of DCA. 4. The addition of KCl to the drinking water of rats receiving DCA and NaCl tended to correct the depression of the level of potassium in the serum, but had no effect upon the hypertension in nephritic animals nor upon the anatomical lesions. 5. The mechanism by which the sodium ion potentiates the activity of DCA has not been established.